From Listening to Recording: Speech Styles Found in Internship Reports - Massao Fairchild, Thomas (2020)
We analyze cases of reported speech in internship reports written by Brazilian Language Arts students with the aim to associate the style employed by them when citing a third party’s speech with the positions they sustain in their texts. We believe that the way in which students report this speech hints at how they “listen” to what goes on in class and how they revisit and organize their own experience by writing about it. That kind of analysis can cast light upon the forms of perception of the school available in academic culture and, all the same, the individual choices made by students when faced with that culture. To analyze our data, we draw from M. Bakhtin (2004, 2015), especially the notions of “linear” and “pictoric” style, the counterpoint between “expression analysis” and “content analysis” and the concept of “bivocal discourse”. We were able to find passages that represent various styles of reported speech but we could hardly find any signs of a particular style being employed to support the construction of a cogent and persistent position. It would seem that reporting teachers’ and students’ speech is influenced by questions that range from phrasing problems to how the author of the report reacts to the speech that is being reported.